Діагностика та лікування соматотропної недостатності у дітей - Вишневська, О. А. (Clinical Endocrinology and Endocrine Surgery, 2011)
The article presents criteria of the diagnostics and results of treatment of children with growth hormone deficiency. Effectiveness of treatment of children with above mentioned deficiency depends on the status of the patient at the time of treatment and on the dose and schedule of administration of recombinant growth hormone. Significant increase in IGF -1 and IGF – binding protein – 3 is seen in the process of treatment with growth hormone in comparison with their background values allows us to use them not only as diagnostic criteria of growth hormone deficiency but also as criteria of effectiveness of treatment with growth hormone as well.